Malaysian undergraduates’ preferences in selecting airlines company - Abdul Aziz, Mohamad Ridhuan; Gunasekaran, Shamany; Yusof, Shuhada; Seow Ting, Thong (2015)
Transportation plays an importance role to moves people and goods from one point to another point. The main transport that used by the people includes buses, cars, train, taxi and airplane. The airline industry has evolved rapidly in recent decades. This research aims to analyses the factor influencing Malaysian undergraduates in selecting airlines. The objective of this study to examines whether ‘price’, ‘service’, ‘route’ and ‘corporate image’ have relationship in selecting airlines. A questionnaire survey on the factor influencing Malaysian undergraduates in selecting airlines was conducted and 384 respondents were analyzed. Correlation and Multiple Regression Analysis were applied on the response collected through the questionnaire instrument. As a result, all hypothesis using the Correlation Analysis are significant. By using Multiple Regression Analysis, there are three (3) hypotheses that have been accepted and one (1) hypothesis have been rejected. To put in a nutshell, with the high services qualities provided by budget airlines together with the price offered, it had increased the recognition of consumers towards airlines. Therefore, it will increase brand choice probability on repurchase intention of consumers. Hence, it will directly affect or influence the decision making of undergraduates in selecting Airlines Company